Analysis of Toddler Eating Patterrn on the Incidence of Stunting in the Coastal Ponelo Islands of North Gorontalo District - Febriyona, Rona; Muhamad, Zuriati; Sali, Nurdiyanti R. (Newinera Publisher, 2024)
Malnutrition especially stunting, is a major public health issue in many parts of the world including the Ponelo Islands of North Gorontalo. Stunting among toddlers is associated with the dietary patterns adopted in the communities and the accessibility of government relations such as the PMT – Supplementary Feeding Program of ‘this area’. Fresh from interviews with health officials, health cadres and parents of stunted children in Ethiopia, the study identified poor dietary diversity and improper feeding schedules as common factors for stunting. Despite enriching enough nutritional support through PMT program, its effectiveness is limited by problems like the erratic implementation and the absence of wide ranging and permanent solutions for the malnutrition problems. The study underscores the necessity of a dual approach, initial nutritional interventions accompanied by a focus on issues affecting pre-school children’s access to nutritious foods, availability and procurement authorities vested in caregivers. By addressing these causes, it becomes possible to empower a community to ensure all children when given opportunity grow to their full potential in eliminating stunting.